EFFORTS TO IMPROVE THE PERFORMANCE OF SECTOR POLICE INTELLIGENCE AS A DETECTION BASE IN REALIZING HARKAMTIBMAS IN THE JURISDICTION OF THE BATANG POLICE DEPARTEMENT - MUHAMMAD SYANDY AL AMIN (Indonesian Journal of Police Studies, 2022)
Writer’s final assignment bringing up an issue about “How are efforts to improve the performance of Police Intelligence as a detection base in supporting Harkamtibmas in the Batang Police Departement”. This Final Project aims to describe the implementation of Sector Police Intelligence as a basis for detection and describe efforts to increase the intelligence capabilities of the Sector Police as a detection base in supporting Harkamtibmas in the jurisdiction of the Batang Police Departement. This study uses a qualitative approach with the type of field research research by conducting limited observations, interviewing resource persons and document studies. In addition, the data used is also obtained from various references such as articles, journal books and relevant online media news. This study uses management theory and the concepts contained in the laws and regulations governing the procedures for implementing Sector Police as the base for detection. In its implementation through the role of the current Police personnel performance is still not optimal due to several factors that are dominant in the human factor and the method applied factor, besides that there are external factors in the form of natural situations so that research is carried out with the aim of being able to identify sector Police performance as a detection base in supporting Harkamtibmas in the jurisdiction of the Batang Police Departement. Efforts to improve the performance of the Polsek Unit as the basis for detection from the Batang Police Departement InteIkam Unit really need to be done to improve performance capabilities through increasing the ability and motivation of personnel, so as to maximize when identifying problems that arise in the context of early detection and early warning. The author advises that the police personnel be given opportunities in the form of regular function training, seek tiered supervision, and provide rewards and punishments to personnel, so that the success of Policce Sector as a detection base can be realized.